2001
DOI: 10.1093/protein/14.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational mapping of the binding surface of a crystalline protein

Abstract: Multiple Solvent Crystal Structures (MSCS) is a crystallographic technique to identify energetically favorable positions and orientations of small organic molecules on the surface of proteins. We determined the high-resolution crystal structures of thermolysin (TLN), generated from crystals soaked in 50--70% acetone, 50--80% acetonitrile and 50 mM phenol. The structures of the protein in the aqueous-organic mixtures are essentially the same as the native enzyme and a number of solvent interaction sites were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
139
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(146 citation statements)
references
References 30 publications
6
139
0
1
Order By: Relevance
“…English et al (9,10) determined high resolution crystal structures of TLN, generated from crystals soaked in aqueous solutions of IPA, ACN, CCN, and IPH, and found that the main substrate specificity pocket (S 1 Ј) of the active site binds all four molecules. IPA also binds to the other three subsites of the active site, and additional sites have been observed for IPA, ACN, and IPH as the concentration of organic solvents in the soaking solution increases.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…English et al (9,10) determined high resolution crystal structures of TLN, generated from crystals soaked in aqueous solutions of IPA, ACN, CCN, and IPH, and found that the main substrate specificity pocket (S 1 Ј) of the active site binds all four molecules. IPA also binds to the other three subsites of the active site, and additional sites have been observed for IPA, ACN, and IPH as the concentration of organic solvents in the soaking solution increases.…”
Section: Resultsmentioning
confidence: 99%
“…This site-mapping and fragment-assembly strategy provides an important approach to drug design (1)(2)(3)(4)(5)(6). Experimental approaches to mapping include x-ray crystallography (7)(8)(9)(10) and NMR techniques (11, l2). In the multiple solvent crystal structure method (7)(8)(9)(10), the x-ray structure of a protein is repeatedly solved in a variety of organic solvents, each representing a different functional group.…”
mentioning
confidence: 99%
See 3 more Smart Citations